Vaginal delivery after cesarean: women's perceptions (Research, Society and Development, 2022)
Objective: To understand the experience of women who have had a normal birth after a cesarean section. Method: Descriptive study with a qualitative approach. Data collection took place between June and October 2019. Twelve women who had at least one normal delivery after a cesarean section were interviewed, in maternity hospitals that exclusively serve SUS in the 17th Health Regional of Paraná. Data were analyzed by thematic content analysis proposed by Bardin. Results: From the analysis, it was possible to apprehend two thematic units that allowed describing the woman's experience with vaginal delivery after a cesarean. Pain was reported as the most striking event for women when experiencing a vaginal delivery, however, it is minimized after the baby is born, generating satisfaction in relation to this type of delivery when compared to cesarean section. The negative perception of vaginal delivery was related to the time of labor. Only two women revealed satisfaction with the cesarean section, and the others reported physical limitations and contact with the newborn, emphasizing the need for help from other people to perform the care of the newborn. Final considerations: Women prefer vaginal delivery, emphasizing faster recovery and independence to care for the baby.